Keberadaan Pengawas Sekolah dalam Peraturan Pemerintah Nomor 57 Tahun 2021 - Aspandi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2021)
This research is motivated by the absence of the word school supervisor in Government Regulation 57 of 2021. The question of this research is how is the existence of school supervisors in Government Regulation 57 of 2021? The purpose of this study was to describe the existence of school supervisors in PP 57 of 2021. This study used a qualitative procedure with the type of literature review research. The primary data sources are Government Regulation number 57 of 2021, Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform number 10 of 2021 and Regulation of the Minister of National Education number 12 of 2007. This research uses documentation techniques to collect data on the existence of school supervisors in Government Regulation 57 of 2021 The results showed that the Government Regulation 57 of 2021 in article 30 paragraph 3 clearly does not find school supervisors as part of the supervisors in educational units. Thus, at the time of the revision of Government Regulation 57 of 2021, the government can re-enter the position of school supervisor